125 STROKE SURVIVOR AND CARER EXPERIENCES OF NAVIGATION OF STROKE SERVICES AND INFORMATION IN IRELAND: AN EXPLORATORY QUALITATIVE INTERVIEW STUDY. (25th October 2022) - Sexton, E; Fowler, K; Byrne, E; Bennett, K
Abstract: Background: Patient navigation of stroke services is challenging, as survivors have diverse and complex needs, and clear care pathways are often lacking, particularly in the post-acute phase. Exploring the views of stroke survivors and main carers is critical to understanding these navigational challenges. Methods: In-depth semi-structured interviews were conducted online or by phone with stroke survivors (n=16) and main carers (n=13) recruited through voluntary organisations and social media. Participants with communication or cognitive difficulties were included, and provided with accessible information materials. Interviews were audio-recorded and transcribed. Framework analysis was used, involving data familiarisation, coding, development of an analytic framework, charting and interpretation. Ryvicker's (2018) behavioral-ecological conceptual framework for patient navigation was used to inform the analytic framework. Results: Barriers to successful patient navigation at the healthcare system level included complex and unclear eligibility criteria for services and entitlements, including arbitrary age limits; geographical variation; and waiting times for services, particularly rehabilitation. Having a skilled or knowledgeable advocate, such as a family member with experience of the healthcare system, was a key enabling factor. Survivors and carers had to be pro-active and "push" or "battle" for needed services and information. Navigation often involved a substantial administrative burden, which survivors and caregivers had to manage in addition to the demands of the stroke itself, the recovery process, and in many cases other co-morbidities. Healthcare provider factors that supported navigation included clear communication with survivors/carers about services and the stroke itself. Staff who specifically supported care co-ordination were helpful, but this tended to be ad-hoc and limited in availability. Conclusion: Dedicated staff to support patient navigation across the care continuum could make a significant difference to stroke survivor access to services and consequently outcomes. Clearer, standardised and more person-centred referrals pathways, that are widely publicised and understood, would also improve access.